2017
DOI: 10.1016/j.jare.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth-promoting activities for bacterial and fungal endophytes isolated from medicinal plant of Teucrium polium L.

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(129 citation statements)
references
References 49 publications
5
109
0
2
Order By: Relevance
“…Endophytic bacteria and fungi are symbiotic microorganisms living inside healthy plant tissues without causing any disease symptoms. Some beneficial endophytes stimulate plant growth by producing plant hormones such as indole-3-acetic acid (Santoyo et al, 2016;Hassan, 2017), improve the tolerance to abiotic stresses (Pandey et al, 2018), or promote the plant immunity against microbial pathogens, insects, and herbivores (Azevedo et al, 2000;Ryan et al, 2008;Li et al, 2015;Bamisile et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic bacteria and fungi are symbiotic microorganisms living inside healthy plant tissues without causing any disease symptoms. Some beneficial endophytes stimulate plant growth by producing plant hormones such as indole-3-acetic acid (Santoyo et al, 2016;Hassan, 2017), improve the tolerance to abiotic stresses (Pandey et al, 2018), or promote the plant immunity against microbial pathogens, insects, and herbivores (Azevedo et al, 2000;Ryan et al, 2008;Li et al, 2015;Bamisile et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…1 [Zhao et al 2015]. Furthermore, Bacillus endophytic strains were isolated from Teucrium polium L. medicinal plant grown in Egypt [Hassan 2017].…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained by other researchers, who have also observed that IAA producing endophytes positively affected the root development of agricultural plants. Hassan et al [2017] observed that IAA producing endophytes used to inoculate the maize seeds increased the root length. It is noteworthly that some studies confirmed that after inoculation with endophytes of agricultural plants, the root length is comparable to the control seedlings or even shorter [Abbamondi et al 2016].…”
Section: The Effect Of Seed Treatment With Bacterial Cultures On Tritmentioning
confidence: 99%
“…1B-7B and Penicillium Tp. 1F-5F could produce IAA, especially when the growth media are supplemented with Ltryptophan as a precursor (Hassan, 2017). In this study, molecular identi cation of the strain was based on 16S rRNA gene sequence and the phylogenetic tree was shown in Fig.…”
Section: Molecular Identi Cation Of the Strainmentioning
confidence: 99%